Value of M-type phospholipase A2 receptor in clinical diagnosis and treatment of membranous nephropathy:recent advances and current controversies - Wang Hui; Jiang Man; Zhang Di; Wang Yu-qin (Linchuang shenzangbing zazhi)
The sensitivity of serum anti-M-type phospholipase A2 receptor antibodies（anti-PLA2 R Abs）is 70%～80% in idiopathic membranous nephropathy and the specificity over 95%.This article reviewed the latest research advances on the pathogenesis,diagnosis,treatment and prognosis of PLA2 R in membranous nephropathy（MN）and discussed some current controversies as well.The positivity of anti-PLA2 R Abs was defined and whether or not positive anti-PLA2 R Abs adequately excluded secondary membranous nephropathy.Also discussed were the issues of whether or not quantifying anti-PLA2 R Abs predicted prognosis and determined the starting,timing and duration of immunosuppressive treatment.The relationship was examined between anti-PLA2 R Abs titer and recurrent and de novo MN in transplanted kidney as well.The goal was to fully understand the significance of PLA2 R in membranous nephropathy and guide clinical practices.